Investigating the Low Paid Workforce: Employment Characteristics, Training and Work-life balance - Skinner, N; King, P (My University, 2008)
The project is focused on identifying the barriers and supports to VET participation for workers from low paid occupations and those with lower levels of education, in the context of changing work-life configurations.
NCVER Working Paper
Keywords: Employment -- Work/life Balance; Employment; Education and Training; Labour market; Employment and unemployment